Pengaruh Aplikasi Mother Cares (MOCA) terhadap Peningkatan Pengetahuan dan Keterampilan Orang Tua dalam Melakukan Stimulasi Tumbuh Kembang Balita Usia 12–18 Bulan - Tri Wahyuni (Jurnal Medika Cendikia, 2017)
Stimulation is a very important need for growth and development of children. The ability of parents in stimulating toddlers can not just appear, it is necessary to provide information with interesting media in order to achieve optimal results. Applications Mother Cares (MOCA) is a smartphone application that contains a guide to stimulate the growth of toddlers. This application is easy to use so it is expected to be a medium to improve the knowledge and skills of parents in stimulating growth of children under five independently. The purpose of this study is to determine the effect of MOCA application to increase knowledge and skills of parents in stimulating the growth of infants aged 12-18 months. This study uses true experiment design with pretest-posttest with control group design. The subjects of this study are 60 parents who had children aged 12-18 months in the Working Area of ​​Ibrahim Adjie Bandung Community Health Center. Sampling is based on probability sampling technique proportionate stratified random sampling. Statistical test using paired t test and Wilcoxon test with significance of test result determined based on p value <0,05. The results showed that there was a significant difference for the scores of parents' knowledge and skills in stimulating growth between the intervention group and the control group with p = 0.004 for knowledge and p <0.001 for skill. The conclusion of this research is the application of MOCA influential in improving the knowledge and skills of parents in stimulating the growth of infants under the age of 12-18 months.